HUBUNGAN KONTROL DIRI DENGAN PERILAKU MEMBOLOS SISWA KELAS XII DI SMAS SEMEN PADANG TAHUN AJARAN 2025/2026 - Vira Evdaburki; Linda Fitria; Desep Pria Pandri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between self-control and truancy behavior of grade XII students at SMAS Semen Padang in the 2025/2026 academic year. The background of this study is based on the increasing truancy behavior carried out by students, which has the potential to disrupt the learning process and academic achievement. Self-control is seen as one of the important factors that can influence students' tendencies to engage in truancy behavior. This study uses a quantitative approach with a correlational method. The research sample consisted of 95 students taken from four grade XII classes proportionally. The instrument used was a Likert scale questionnaire to measure the level of self-control and truancy behavior. Data were analyzed using normality tests, linearity tests, and Pearson Product Moment correlation tests. The results of the normality test showed that the data were normally distributed with a significance value of 0.085 (> 0.05). The results of the linearity test showed that the relationship between the two variables was linear with a significance value of deviation from linearity of 0.638 (> 0.05). The results of the correlation test showed a significant negative relationship between self-control and student truancy behavior, with a correlation coefficient of -0.416 and a significance value of 0.000 (<0.05). This means that the higher a student's level of self-control, the lower their tendency to truancy. Based on these findings, it is concluded that self-control plays a significant role in suppressing student truancy behavior. Therefore, guidance and counseling teachers, subject teachers, and school officials need to pay attention to helping students improve self-control through psychological guidance and character development programs. This study can also serve as a reference for future researchers to develop studies related to truancy behavior by considering other relevant factors.